1992
DOI: 10.1111/j.1745-6584.1992.tb01529.x
|View full text |Cite
|
Sign up to set email alerts
|

Results of Two Pumping Tests in Wisconsin Age Weathered Till in Iowa

Abstract: Glacial till overlies many bedrock aquifers in Iowa, and a number of landfills and leaking underground storage tank sites are located in weathered and unweathered till. To investigate the potential for significant lateral ground‐water flow in Wisconsin age weathered loam till in Iowa, two 24‐hour pumping tests were performed in the shallow unconfined ground water present in the weathered till, a constant flowrate pumping test and a constant drawdown pumping test. The saturated thickness in the weathered till a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 16 publications
1
33
0
Order By: Relevance
“…These processes may produce fast transport pathways to underlying aquifers. Diffusive flow through massive clays in glacial tills may also occur (Jones et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…These processes may produce fast transport pathways to underlying aquifers. Diffusive flow through massive clays in glacial tills may also occur (Jones et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The differences in sample size and clay content may account for the differences in magnitude of hydraulic conductivity values. The high value of hydraulic conductivity measured at this site with in situ pumping tests relative to that measured by Hendry, 1988 with pumping tests may be a result of differences in parent material (Jones et al, 1992). The Canadian till has a grain size distribution of 10% sand, 33% silt, and 57% clay with clay texture (Fernandez and Quigley, 1991).…”
Section: Discussionmentioning
confidence: 91%
“…It has been shown that due to the interconnectivity of the fractures and macropores contaminants may travel preferentially through a natural clayey till . Preferential transport that occurs in these natural clayey tills indicates that soils of this type cannot be thought of as a banier for contaminants (Jones, 1992). Thus, an understanding on the genesis of fractures and macropores is essential for understanding this preferential flow occunring in glacial tills and other engineering properties.…”
Section: Identification Of Fractures and Macropores In Glacial Tillsmentioning
confidence: 99%
See 2 more Smart Citations